Bagaimana Purna Ketua PR IPM SMA/K se-Prambanan Sleman Memaknai Pengalaman Organisasi dalam Membentuk Identitas Diri - Mita Andriani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to gain a deeper understanding of how former Chairpersons of the Muhammadiyah Student Association (Ikatan Pelajar Muhammadiyah/IPM) Branch Leadership (PR IPM) in the Prambanan, Sleman area interpret their organizational experiences. It also explores the influence of their involvement in IPM that continues to shape their lives, particularly in terms of communication skills. This study employed a qualitative approach using a phenomenological method. The participants consisted of four former General Chairpersons of PR IPM in the Prambanan, Sleman area, selected through purposive sampling based on the criteria that they had completed their term of office at least one year prior to the study. Data were collected through in-depth interviews. The findings reveal a significant contrast in the participants' self-concepts. Before joining IPM, they described themselves as passive and shy students. However, through their organizational experiences, they developed into confident and responsible individuals, and these characteristics have persisted after the end of their leadership period. The study concludes that the former chairpersons have developed a new self-identity, characterized by better emotional control, time discipline, and the ability to communicate politely and effectively.